Adverse Outcome in a Near Term, High-Risk Twin Pregnancy Complicated by COVID-19: A case report - Razmaeda Sarastry; Crismanto Layarta; Ussisti Aladini; Alini Hafiz; Besari Adi Pramono (Faculty of Medicine, Diponegoro University, 2020)
Background: COVID-19 affecting the outcome of pregnancy is still under investigation. Here we report a case of primigravida with monochorionic diamniotic twin pregnancy with superimposed preeclampsia who develop symptoms of COVID-19 infection on her near term pregnancy and was confirmed later on as COVID-19 positive after cesarean section. The pregnancy was terminated abdominally due to the intrauterine fetal demise of both twins using COVID-19 standard equipment.Case Presentation: A 29-year-old female, gravida 1, para 0 presented with a twin pregnancy at the gestational age of 36 weeks was referred to our emergency department for further management of intrauterine fetal death of both twins. Six days before admitted to our emergency department, she has been experienced a remittent fever which followed by a mild cough. Four days before admission, she complained of decrease movement of the babies. She went to the Secondary Hospital to check her pregnancy and both fetal heart rates were not found. The patient is obese (BMI 49.2 kg/m2) and had prior uncontrolled hypertension but no other medical history, including epilepsy, allergies, asthma, heart disease as well as Diabetes Mellitus.Conclusion: A research about placental pathology in pregnancy with confirmed case of COVID-19 infection showed no pathognomonic feature in the histopathologic examination but mostly, there were maternal vascular malperfusion (decidual arteriopathy in particular) and intervillous thrombi. In the end, a further examination is suggested to evaluate the course and causal factors pertaining to this case.